PENGARUH KARAKTERISTIK PERSONALITAS MANAJER TERHADAP HUBUNGAN ANTARA PARTISIPASI DALAM PENYUSUNAN ANGGARAN DENGAN KINERJA MANAJERIAL - Wirjono, Endang Raino; Raharjono, Agus Budi (KINERJA, 2007)
This research examined the effects of budget participation on performance of manager in firms. Prior studies in participative budgeting suggest that personality characteristic is potential ly important explanatory variables to motivate manager achieving good performance. Data were col lected from 85 managers of firms in Yogyakarta. Results of this study indicated that interaction betweenÂ need of independence and participation had significant impact on managerial performance. This research also proved that interaction between need of authority and participation in setting budgeting had significant impact on managerial performance.Keywords: need of independence, need of authority, participative budgeting, managerial performance